Geriatrics Health - Çakmur, Hülya (IntechOpen, 2018)
Aging is characterized by functional decline in every organ due to several cellular, biological, and physiological changes over time. Molecular and cellular damages are gradually decreasing in the physical and mental capacities of the human body. Health results have shown that lifespan has dramatically increased during the twenty-first century. Increasing elderly population naturally deals with many health problems leading to a rise in health expenditure and labor loss. The good news is that the clinical trials in gene therapy have almost stopped and/or reversed human aging. Regenerative medicine can repair and reverse aging in all body cells. Thus, the body's own repair mechanisms may struggle with aging and age-related diseases. Research is promising and suggests that human aging will be eradicated on earth.